Home Sweet Sewn - Butcher, Alice and Farquhar, Ginny (Newton Abbot David & Charles, 2009)
Home Spun Sensations is packed with ideas and inspiration to add a unique homespun look to your home d? cor. Create fabulous projects with designs that reflect all aspects of your home and lifestyle, from cozy cushions and throws to an eye-catching apron. Plus, explore a variety of easy-to-follow techniques that include patchwork, quilting, applique, rag rug twining, embroidery, and sewing with oilcoth. With designs that represent every season, you are sure to find something to fit your own personal style.
Include Colored Illustrations and Index.
Keywords: Sewing